(untitled) (Bangladesh Critical Care Journal, 2021)
Coronavirus Disease 2019 (COVID-19) has become a pandemic since March 2020.Kidney-transplant recipients appear to be at particularly high risk for critical COVID-19 illness due to chronic immunosuppression and coexisting conditions. We report a case of a young lady who being a renal allograft recipient developed concomitant COVID-19 and Cytomegalovirus (CMV) infection. Bangladesh Crit Care J March 2021; 9(1): 56-58